The AUX1 LAX family of auxin influx carriers is required for the establishment of embryonic root cell organization in Arabidopsis thaliana - Ugartechea-Chirino, Yamel (Oxford University Press, 2010)
BACKGROUND AND AIMS: The root meristem of the Arabidopsis thaliana mature embryo is a highly organized structure in which individual cell shape and size must be regulated in co-ordination with the surrounding cells. The objective of this study was to determine the role of the AUX1 LAX family of auxin import carriers during the establishment of the embryonic root cell pattern. METHODS: The radicle apex of single and multiple aux1 lax mutant mature embryos was used to evaluate the effect of this gene family upon embryonic root organization and root cap size, cell number and cell size. KEY RESULTS: It was demonstrated here that mutations within the AUX1 LAX family are associated with changes in cell pattern establishment in the embryonic quiescent centre and columella. aux1 lax mutants have a larger radicle root cap than the wild type and this is associated with a significant increase in the root-cap cell number, average cell size, or both. Extreme disorganization of the radicle apex was observed among quadruple aux1 lax1 lax2 lax3 mutant embryos, but not in single aux1 null or in lax1, lax2 and lax3 single mutants, indicating redundancy within the AUX1 LAX family. CONCLUSIONS: It was determined that the AUX1 LAX family of auxin influx facilitators participates in the establishment of cell pattern within the apex of the embryonic root in a gene-redundant fashion. It was demonstrated that aux1 lax mutants are affected in cell proliferation and cell growth within the radicle tip. Thus AUX1 LAX auxin importers emerge as new players in morphogenetic processes involved in patterning during embryonic root formation.